RRx-001, a downregulator of the CD47- SIRPα checkpoint pathway, does not cause anemia or thrombocytopenia. (3rd April 2021) - Oronsky, Bryan; Cabrales, Pedro; Caroen, Scott; Guo, Xiaoning; Scribner, Curtis; Oronsky, Arnold; Reid, Tony R.
ABSTRACT: Introduction : The CD47 and SIRPα checkpoint pathway has garnered much interest within the anti-cancer research community, with multiple experimental checkpoint inhibitors targeting CD47 and SIRPα in development. The use of such checkpoint inhibitors may however be limited by hematologic toxicity. Areas covered : We report on RRx-001, the first known small molecule downregulator of CD47 and SIRPα, which has shown a lack of hematologic toxicity in clinical trials. Expert opinion : RRx-001 is the first reported small molecule downregulator of CD47 and SIRPα and lacks any notable hematologic or systemic toxicity as demonstrated in clinical trials to date. Small molecule RRx-001 could be used in combination with or in place of CD47 targeting antibodies for anti-cancer treatment.